Implementation of The Elderly Health Monitoring Information System (MIS-Elderly) Rapid Application Development: Implementasi Sistem Informasi Pemantauan Kesehatan Lansia (SIP-Lansia) Rapid Application Development - Ria Yusian TB, Desita; Rosdiana, Eva; Rezeki, Sahbainur; Ardian, Zalfie (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
The advancement of information and communication technology (ICT) has grown increasingly modern, expanding the demand for information. One effective way to provide optimal services to the public is through fast and accurate information delivery, which can be achieved by implementing information systems, particularly in healthcare services. However, not all aspects of healthcare services, such as elderly health posts (Posyandu Lansia), have adopted information systems to assist in real-time health monitoring. The elderly population is at high risk of developing various health conditions, such as hypertension, arthritis, rheumatism, and tuberculosis, which require routine care and monitoring. Therefore, this community service initiative aims to implement a health monitoring information system for the elderly using the Rapid Application Development (RAD) approach, enabling both the elderly and their families to monitor health effectively. The community service methods involve providing education on elderly health, raising awareness about the importance of health monitoring, and implementing and supporting the use of the information system among the elderly and their families. As a result of this program, the elderly gained knowledge about health and the importance of regular health monitoring. Furthermore, both the elderly and their families are now able to conduct health monitoring through the Elderly Health Monitoring Information System (SIP Lansia).